Effect of chemical components in white liquor on carbon activation. (31st July 2015) - Namazi, Azadeh B.; Allen, D. Grant; Jia, Charles Q.
<x xml:space="preserve">Abstract</x> Conversion of pulp mill sludge into activated carbon is an alternative solution for waste management at pulp mills. In this study, the use of white liquor as an activating agent was investigated, with the aim of applying an available source at pulp mills. A Specific Surface Area (SSA) value of 650 m2/g and an activation yield of 61 % were achieved with synthetic white liquor at 600 °C and 2 h. The SSA values obtained with white liquor were ∼60 % lower than those with NaOH alone. Thermodynamic analyses, X‐ray diffraction, and elemental analyses showed that both Na2S and Na2CO3 inhibit the activation reaction with carbon.